Paul of Tarshish: Isaiah 66.19 and the Spanish Mission of Romans 15.24, 28 - Das, A. Andrew (New Testament studies, 2008)
Interpreters of Paul's Letter to the Romans frequently identify preparations for the Spanish mission—mentioned within only two verses at the end of the letter—as the primary reason for writing. Paul's extensive use of Isaiah suggests to some that he viewed Spain as the fulfillment of the reference to ‘Tarshish’ in Isa 66.19. The Hebrew Bible, however, does not provide any evidence that Tarshish is in Spain rather than in Cilicia. Evidence is lacking in the Hellenistic and Roman eras for a Spanish Tartessos–Tarshish connection. The Spanish mission thesis also overemphasizes the importance of Rom 15.24, 28.